Relationship of Serum Tau Levels with Cognitive Functions and Factors Affecting The Cognitive Function Decrease in Parkinson's Disease Patients - Meldayeni Busra; Yuliarni Syafrita; Hendra Permana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: Cognitive impairment is a non-motor symptom of Parkinson's disease (PD) which occurs as the disease progresses and affects quality of life. Many efforts have been developed in early detection of cognitive disorders, one of which is the examination of tau protein biomarkers, where the tau protein that undergoes pathological changes to form neurofibrillary tangles (NFTs) is found in Alzheimer's disease and PD and plays a role in cognitive impairment. However, the role of tau in PD is still controversial. This study aims to assess the relationship between serum tau levels and cognitive function and the factors that affect cognitive function in PD patients. Methods: This cross-sectional design was conducted at the RSUP DR. M Djamil Padang. During the period March to August 2020, 62 research subjects were obtained. Cognitive function examination was carried out by using the MoCA-Ina test and examination of serum tau levels using the Elisa method. The relationship between categorical variables was tested by Chi square and differences in serum tau levels in the group with and without cognitive impairment were tested with the Mann Whitney test, considered statistically significant if the p value <0.05. Results: With Moca Ina examination, it was found that 67.7% of patients had impaired cognitive function. The mean serum tau level was 198.004 ± 162.69 ng / L.There was a significant relationship between education level and degree of disease with cognitive function (p <0.05) and there was no difference in mean serum tau levels between groups with and without cognitive impairment. Conclusion: There is a significant relationship between education level and degree of disease with cognitive function and there is no difference in mean serum tau protein levels between the cognitive impaired group and the cognitive normal group.